Merleau-Ponty and a phenomenology of PTSD hidden ghosts of traumatic memory - McDonald, MaryCatherine 1981- (Lexington Books, 2019)
Despite the fact that we have been studying posttraumatic stress disorder (PTSD) since at least the late 1800s, it remains prevalent and, in many cases intractable. 'Merleau-Ponty and a Phenomenology of PTSD: Hidden Ghosts of Traumatic Memory' begins with the assertion that we struggle to successfully treat PTSD because we simply do not understand it well enough. Using the phenomenological approach of Maurice Merleau-Ponty - which focuses on the first-person, lived experience of the trauma victim - 'Merleau-Ponty and a Phenomenology of PTSD: Hidden Ghosts of Traumatic Memory' focuses on reframing our understanding of combat trauma in two fundamental ways. The concepts of embodiment and adaptation give us an understanding of the human being as fundamentally adaptive. This allows us to view traumatic responses as adaptive as well. When the roots of traumatic injury become reframed in this way, combat-related PTSD can be understood more accurately as a set of symptoms borne of strength and survival rather than weakness or disorder